ULAMA MINANGKABAU DI PENTAS SEJARAH TANAH DELI PADA ABAD 20 M - Bahri, Samsul; Suri, Nursukma; Suprayitno, Suprayitno (Puteri Hijau : Jurnal Pendidikan Sejarah, 2025)
This research aims to determine the progress of Minangkabau ulama in Tanah Deli, especially in the 20th century AD. This research method was carried out through four stages, namely data collection (heuristics), source examination (verification), interpretation (interpretation), and writing (historiography). carried out based on field research and library research. The research results show that the presence of the Minangkabau ethnic group in Tanah Deli in the 20th century AD was inseparable from the impact of the open door political economy which made Tanah Deli a large economic area in the East Sumatra region. The economic growth in Tanah Deli has been able to attract migrants from various regions, including the Minangkabau ethnic group, to come to Tanah Deli. These Minangkabau ethnic migrants have always been identified with the Muhammadiyah organization because they had previously been influenced by Muhammadiyah when they were still in their hometown. Then when they were in Tanah Deli they made Muhammadiyah a gathering place for Minangkabau migrants who had a modernist religious style. However, for certain reasons their existence did not receive full political support from the Malay Sultanate or the Dutch East Indies government. However, the Minangkabau ethnic group has colored the history of Tanah Deli, especially in the religious sector, which is marked by the emergence of many big-name scholars from the Minangkabau ethnic group, namely Bustami Ibrahim, Hamka, Mahyaruddin Salim, Joesoef Sou'yb, Mansyur Luthan, Saldin Saleh, Djamaluddin Ahmad , Anas Nurdin, and Firdaus Naly.